The 4 vectors of innovation: A framework for the strategic management of design (Estudos em Design, 2015)
This theoretical and exploratory essay, using a qualitative, historical and documental approach, aims to present a multi-vector framework of innovation to be adopted by strategic design management. To this end, theories about creativity and innovation are reviewed, principles of innovation management methods and techniques are discussed, and numerous determinants and consequents of innovation already empirically investigated are organized. The visual synthesis of the results presents the four strategic vectors of design discerned according to their measurable outcomes: 1) the design as a means of optimizing the shapes of products or processes and generate savings; 2) the design as a means of triggering collective sentiments and generate sympathy; 3) the design as a means of establishing organizational cultures and generate harmony; and 4) the design as a means to fit the facts and generate ergonomics.
Keywords: Design Management; Innovation; Strategy; Framework